Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Pada Sentra Batik Wastralingga Kabupaten Purbalingga - Purnomo, Dinnas (DFAME Digital Financial Accounting Management Economics Journal, 2025)
This study aims to analyze and determine the effect of Product Quality and Price on Customer Satisfaction, so that it becomes a suggestion for solving the Wastralingga party's problems and can be used as additional literacy for further research. The research method used is quantitative, questionnaire data of 77 respondents came from consumers of Sentra Batik Wastralingga. The sampling technique used stratified random sampling. Questionnaire data was measured using a Likert scale. This study uses multiple linear analysis with the help of the SPSS version 26 program. The results of this study indicate that the variables of product quality and price have a significant effect on customer satisfaction at "Sentra Batik Wastralingga"